Konstruksi Etika Publik dalam Tata Kelola Algoritma Media Sosial di Masyarakat Demokratis - Alatas, Muhtar; Jaya, Syafrie Mangun; Khalid, Ihdam (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Social media algorithms have become central actors in shaping the digital public sphere in democratic societies. Through mechanisms of curation, recommendation, and content moderation, algorithms influence the distribution of information, the formation of public opinion, and patterns of civic participation. This study aims to analyze the construction of public ethics in the governance of social media algorithms by positioning it as a normative, structural, and institutional issue. The main focus is on how the principles of justice, transparency, and accountability are articulated and implemented in algorithmic management practices by digital platforms. This study adopts a qualitative approach with a normative critical research design and conceptual analysis. Data are obtained through a systematic literature review of academic studies, policy reports, and institutional documents relevant to platform economies, digital regulation, and algorithmic ethics. The analysis links conceptual empirical findings with frameworks of public ethics and democratic governance. The findings indicate that current social media algorithm governance is still dominated by commercial logic and technical efficiency, which marginalize public ethical considerations. This condition produces transparency deficits, weak accountability mechanisms, and increasing power asymmetries between platforms and users. This study underscores the need to reconstruct algorithm governance by positioning algorithms as digital public infrastructure. Such reconstruction requires systematic policy intervention, meaningful public participation, and the strengthening of social justice principles to safeguard the quality of democracy in the digital era.